PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MATERI MEMBACA UNTUK MELALUI MODEL CIRC DI SMP NEGERI 1 INDRA MAKMU - ., Wartem (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this study is to improve the ability of VII grade students of SMP Negeri 1 Indra Makmu to read intensively to find the main ideas in the text through the CIRC Model. The types of data in this study are of two kinds, namely qualitative data and quantitative data. Qualitative data is obtained through observation techniques, while quantitative data is obtained through test techniques. The method used is descriptive method while the data processing technique is through a single frequency distribution. Based on the results and discussion starting from awa condition. This research began in January to April 2018, which was held in class VII of the second semester of SMP Negeri 1 Indra Makmu. The type of research is Class Action Research with two cycles, each cycle consisting of: planning, implementation, observation and reflection. The data collection techniques and tools in this study used descriptive analysis techniques for data in the form of student work documents, and observation sheets. Before the research was conducted the average value of students towards Intensive Reading skills was only 61.25 with learning completeness from 24 students, only 10 students (41.67%) were complete. In the first cycle student learning outcomes began to increase by 71.67 with mastery learning as many as 17 students (70.83%) were completed. In the second cycle learning outcomes increased sharply to 82.08 with the number of students completing 23 students (95.83%). Based on the achievement of learning outcomes, it can be concluded that the use of the CIRC model can improve the learning outcomes of Indonesian Intensive Reading material to find the main ideas in the text for class VII students in semester II at Indra Makmu State Middle School 2017/2018 Academic Year.